Politisch-institutionelle Determinanten aktionärsorientierter Reformen - Martin Höpner (Max Planck Institute for the Study of Societies, 2005)
This text is a preliminary study on the political-institutional determinants of shareholder oriented reforms in 21 OECD countries. I analyse stock and flow data on the development of stock market capitalization and on the rights of minority shareholders (La Porta et al. index) between 1990 and 2000 respective 2002. Six groups of dependent variables are distinguished: (1) economic, (2) structural, (3) cultural variables; (4) the political composition of governments; (5) institutions of consociational democracy and (6) labor relations. The analysis shows that there is a strong empirical relationship between shareholder oriented reforms and the importance of private pension schemes. In 1990, high shareholder protection was typical for countries with conservative and liberal governments, while low shareholder protection was a particular feature of catholic countries. This empirical relationship declined during the 1990s. As a consequence of weak reforms in the Nordic countries, minority shareholder protection in the year 2000 was comparatively low in countries governed by Social Democratic parties. Reforms went further in pluralist rather than corporatist countries. I use these preliminary results to identify further need for research. Most urgently, more comparative indexes on corporate governance features - such as takeover regulation and shareholder democracy - need to be developed. – – Dieser Text beschreibt eine explorative Vorstudie zu den politisch-institutionellen Determinanten aktionärsorientierter Reformen im Vergleich von 21 OECD-Ländern. Als abhängige Variablen dienen Daten zur Entwicklung der Marktkapitalisierungen sowie der La-Porta-et-al.-Index, der die Reichweite von Aktionärsrechten abbildet. Es werden Stocks für die Jahre 1990 und 2000 bzw. 2002 sowie Flows für die neunziger Jahre untersucht. Sechs Gruppen potenziell erklärungskräftiger Variablen werden unterschieden: (1) wirtschaftliche, (2) strukturelle, (3) kulturelle Variablen; (4) parteipolitische Regierungszusammensetzung; (5) verhandlungsdemokratische Institutionen; sowie (6) Arbeitsbeziehungen. Es zeigt sich ein enger Zusammenhang zwischen aktionärsorientierten Reformen und dem Stellenwert privater Altersvorsorge. Noch 1990 standen vor allem konservative und liberale Regierungen für ausgebaute, katholische Länder hingegen für schwach entwickelte Aktionärsrechte; diese Zusammenhänge haben sich in den neunziger Jahren abgeschwächt. Wegen geringer Reformtätigkeit in den nordischen Ländern wiesen sozialdemokratisch geprägte Länder im Jahr 2000 vergleichsweise schwache Aktionärsrechte auf. Reformen fielen umso weit reichender aus, je pluralistischer die Interessengruppensysteme der betreffenden Länder organisiert waren. Diese vorläufigen Ergebnisse werden genutzt, um weiteren Forschungsbedarf zu identifizieren, der im Rahmen eines größeren Projektzusammenhangs abzuarbeiten ist. Forschungsbedarf liegt vor allem in der Erfassung und Codierung weiterer Dimensionen der Unternehmenskontrolle wie der Übernahmeregulierung und der Aktionärsdemokratie.
Keywords: 300